The influence of study population and definition of improvement on the smallest detectable change and the minimal important change of the neck disability index - Schuller, Wouter (BioMed Central, 2014)
BACKGROUND: Reported values of the minimal important change (MIC) and the smallest detectable change (SDC) for the neck disability index (NDI) differ strongly, raising questions about the generalizability of these parameters. The SDC and the MIC are possibly influenced by the study design or by the study population. We studied the influence of the type of anchor, the definition of improvement and population characteristics on the SDC and the MIC of the NDI. METHODS: A cohort study including 101 patients with non-specific, chronic neck pain. SDC and MIC were calculated using two types of external anchors. For each anchor we applied two different definitions to dichotomize the population into improved and unimproved patients. The influence of patient characteristics was assessed in relevant subgroups: patients with or without radiating pain and patients with different baseline scores. RESULTS: The influence of different anchors and different definitions of improvement on estimates of the SDC and the MIC was only minimal. The SDC and the MIC were similar for subgroups of patients with or without radiation, but differed strongly for subgroups of patients with higher or lower baseline scores. CONCLUSIONS: Our study shows that estimates of the SDC and the MIC of the NDI can be influenced by population characteristics. It is concluded that we cannot adopt a single change score to define relevant change by combining the result of previous studies.